Clinical medicine a practical manual for emergency medicine and tropical diseases - Rewari, BB; Jain, DG; Chawla, ,MPS (Jaypee Brothers Medical Publishers (P) Ltd, 2014)
In view of the rapid advances in the field of internal medicine every year, this book basically focuses on "emergency and tropical medicine". Besides the proceedings of the conference, this book also includes other topics of day-to-day clinical importance, thus making it more comprehensive and relevant for the readers. Common illnesses seen by the internists in the emergency room form the backbone of this Update. Key issues are described in a lucid manner by eminent clinicians, master teachers, and stalwarts from all over the country